Effect of Follicular Proteins on Buffalo Sperm Functions during Cryopreservation - KUMARESAN, A; ANSARI, M R; GARG, ABHISHEK (The Indian Journal of Animal Reproduction, 2023)
A study was undertaken to assess the effect of follicular proteins on freezability of buffalo spermatozoa. Follicular fluid was aspirated from the follicles (>5mm) of buffalo ovaries obtained from slaughterhouse. The follicular fluid was centrifuged (3000 rpm; 30 minutes), filtered (0.2μ) and frozen at - 20°C. The proteins in pooled follicular fluids were precipitated over night t. sing ammonium sulphate, centrifuged ( I 0000 rpm; 30 minutes) and dialyzed (> I 0kDa). After protein estim:1tion, aliquots of samples containing IO mg proteins were lyophilized in cryovials and stored frozen at -20°( ’)ix pooled good quality ejaculates from two Murrah buffalo bulls were used as split ejaculates. After r 1 semen analysis, each pooled ejaculate was splited into five parts and extended in Tris-Egg yolk-Citrate l ·.tr 1 er (2( ’ egg )Olk: 7% glycerol), so that final diiution yielded approximately 60 million sperm per ml and . -yopres, rved in 0.5 ml French straws (30 million sperm cells/straw) in LN2 (-I 96°C). Prior to freezing, one pa1i of eaL,1 ejaculate was added with follicular proteins at the rate of lmg/ml of extended semen while another patt w, , froze without any added proteins (control). Semen samples (pre-freeze· and frozen-thawed) were evaluated fo. motility, viability and intact acrosome percentages, sperm penetration distance in cervical mucus (BCMPT) and swollen sperm percentage in response to hypo-osmotic solution (HOSST). Besides this, frozen thawed sperms were washed and incubated in spe,m-T ALP at 37°c for 6 hrs. The sperm motility, viability and. intact acrosome percentages were evaluated at hourly interval. Addition of follicular proteins maintained significantly (P<0.05) higher post-thaw motility, viability and acrosomal integrity percentages than the control. Similarly the BCMPT and HOSST values were also higher in follicular protein added group than the control group. Sperm motility and viability percentages were significantly (p<0.05) higl ,. through out the incubation period in the follicular protein treated group than the control group. But, the o1c ·nd was not observed in case.of sperm acrosomal integrity percentage. It was inferred that inclusion c ,olli- iar proteins before freezing had beneficial effects’ on post thaw characteristics of buffalo spermatozoa.